2013
DOI: 10.1371/journal.pone.0065312
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Porcine Parvovirus Tentatively Designated PPV5

Abstract: A new porcine parvovirus (PPV), provisionally designated as PPV5, was identified in U.S. pigs. Cloning and sequencing from a circular or head-to-tail concatemeric array revealed that the PPV5 possesses the typical genomic organization of parvoviruses with two major predicted open reading frames (ORF1 and ORF2), and is most closely related to PPV4 with overall genomic identities of 64.1–67.3%. The amino acid identities between PPV5 and PPV4 were 84.6%–85.1% for ORF1 and 54.0%–54.3% for ORF2. Unlike PPV4, but si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 52 publications
4
78
4
2
Order By: Relevance
“…These results indicated the presence of a possible novel parvovirus. On the basis of its homology to parvoviruses and its swine host, this DNA virus was tentatively named porcine parvovirus type 6 (PPV6) after the two recently identified PPVs; i.e., PPV4 and PPV5 (data not shown) [12,21]. Attempts to stably passage the PPV in PK15 (swine kidney), Vero (African green monkey kidney), and Marc 145 (fetal rhesus monkey kidney) cells were unsuccessful (data not shown).…”
Section: −9mentioning
confidence: 99%
See 4 more Smart Citations
“…These results indicated the presence of a possible novel parvovirus. On the basis of its homology to parvoviruses and its swine host, this DNA virus was tentatively named porcine parvovirus type 6 (PPV6) after the two recently identified PPVs; i.e., PPV4 and PPV5 (data not shown) [12,21]. Attempts to stably passage the PPV in PK15 (swine kidney), Vero (African green monkey kidney), and Marc 145 (fetal rhesus monkey kidney) cells were unsuccessful (data not shown).…”
Section: −9mentioning
confidence: 99%
“…They also differed from other parvoviruses by their relatively large predicted VP protein. These analyses indicated that PPV6 viruses are likely to belong to the novel genus Copiparvovirus within the subfamily Parvovirinae [12]. Pairwise comparisons were performed for the nucleotide sequences and predicted amino acids sequences of PPV6 with other parvoviruses.…”
Section: −9mentioning
confidence: 99%
See 3 more Smart Citations